Nephron deficit and low podocyte density increase risk of albuminuria and glomerulosclerosis in a model of diabetes - Sarah E. Gazzard; James van derWolde; Kotaro Haruhara; John F. Bertram; Luise A. Cullen‐McEwen (Physiological Reports, 2023)
Abstract Podocytes are terminally differentiated epithelial cells in glomeruli. Podocyte injury and loss are features of many diseases leading to chronic kidney disease (CKD). The developmental origins of health and disease hypothesis propose an adverse intrauterine environment can lead to CKD later in life, especially when a second postnatal challenge is experienced. The aim of this study was to examine whether a suboptimal maternal environment would result in reduced podocyte endowment, increasing susceptibility to diabetes‐induced renal injury. Female C57BL/6 mice were fed a low protein diet (LPD) to induce growth restriction or a normal protein diet (NPD) from 3 weeks before mating until weaning (postnatal Day 21, P21) when nephron and podocyte endowment were assessed in one male and one female offspring per litter. Littermates were administered streptozotocin or vehicle at 6 weeks of age. Urinary albumin excretion, glomerular size, and podometrics were assessed following 18 weeks of hyperglycemia. LPD offspring were growth restricted and had lower nephron and podocyte number at P21. However, by 24 weeks the podocyte deficit was no longer evident and despite low nephron endowment neither albuminuria nor glomerulosclerosis were observed. Podocyte number was unaffected by 18 weeks of hyperglycemia in NPD and LPD offspring. Diabetes increased glomerular volume reducing podocyte density, with more pronounced effects in LPD offspring. LPD and NPD diabetic offspring developed mild albuminuria with LPD demonstrating an earlier onset. LPD offspring also developed glomerular pathology. These findings indicate that growth‐restricted LPD offspring with low nephron number and normalized podocyte endowment were more susceptible to alterations in glomerular volume and podocyte density leading to more rapid onset of albuminuria and renal injury than NPD offspring.